Sustained reduction in circulating cholesterol in adult hypopituitary patients given low dose titrated growth hormone replacement therapy: a two year study. - Florakis, D; Hung, V; Kaltsas, G; Coyte, D; Jenkins, P; Chew, S; Grossman, AB; Besser, G; Monson, J (2000)
OBJECTIVE: To study the effects of short (6 months) and longer-term (up to 24 months) growth hormone (GH) replacement therapy using a dose titration regimen, on lipid and glucose metabolism in GH-deficient, hypopituitary adults. DESIGN: On-going open study of GH treatment up to 24 months. Measurements were performed at baseline and at 6, 12, 18 months and 2 years during therapy (data shown at 6 months and 2 years only). Using a dose titration regimen the median GH dose used to achieve and maintain IGF-I levels above the median, but below the upper limit of the age-related reference range (median IGF-I 202.5 microg/l, range 76-397 microg/l), was 1.2 IU daily (range 0.4-3 IU) [0.8 IU/day, males; 1.6 IU/day, females]. PATIENTS: Ninety GH-deficient hypopituitary adults (54 female, median age 48 years, range 19-79 years) entered the study and 24 (14 female, median age 45 years, range 32-79 years) have concluded the 2 year period of assessment. MEASUREMENTS: Body mass index (BMI), waist and hip circumference ratio (WHR), fasting lipids, glucose and glycated haemoglobin (HbA1c) levels were measured at 6 month intervals during GH therapy. RESULTS: Using the dose titration regimen, compared to pretreatment values, total and low density lipoprotein (LDL)-cholesterol levels were significantly lower at 6 months (mean +/- SEM, 5.61+/-0.1 vs. 5.25+/-0.1, and 3.85+/-0.19 vs. 3.43+/-0.26, respectively, P<0.05), and were maintained throughout the study. Male patients had significantly lower pretreatment total and LDL cholesterol levels than females (mean +/- SEM, 5.33+/-0.16 mmol/l vs. 5.7+/-0.12 mmol/l and 3.8+/-0.23 mmol/l vs. 3.92+/-0.29 mmol/l, respectively, P< 0.05). A decrease in total cholesterol was confined to patients with pretreatment total cholesterol levels above 5.8 mmol/l; patients with the highest pretreatment cholesterol levels (> 6.4 mmol/l) obtained the greatest cholesterol reduction (mean +/- SEM, 7.13 +/- 0.14 mmol/l vs. 5.76+/-0.31 mmol/l, P<0.05). A cholesterol-lowering effect of GH therapy was evident in patients who had elevated pre-GH total cholesterol levels even if they were already receiving and continuing lipid lowering medication (mean +/- SEM, 5.62+/-0.22 vs. 5.03+/-0.285, P<0.05). A modest increment in high density lipoprotein (HDL)-cholesterol was evident at 18 months but there was no significant change in triglycerides at any time point. Fasting plasma glucose increased significantly at 6 months but remained within the reference range. Glycated haemoglobin increased significantly at 6 months and was maintained throughout the study; one patient developed frank diabetes mellitus while receiving treatment. There was a weak but significant correlation between the increment in glycated haemoglobin and pretreatment BMI (r = + 0.215, P<0.05). CONCLUSION: The effect of GH on lowering total and low density lipoprotein-cholesterol is more prominent in patients with higher pretreatment cholesterol levels and is evident even in patients receiving other lipid-lowering medication. A modest increment in mean fasting glucose (within the reference range) and mean glycated haemoglobin persisted throughout the study. One patient developed diabetes mellitus. A GH replacement regimen using low dose and careful titration to avoid elevated IGF-I levels and adverse effects is associated with sustained beneficial effects on circulating lipids.